2012
DOI: 10.1016/j.lungcan.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic surfaceome analysis of mesothelioma

Abstract: Identification of new markers for malignant pleural mesothelioma (MPM) is a challenging clinical need. Here, we propose a quantitative proteomics primary screen of the cell surface exposed MPM N-glycoproteins, which provides the basis for the development of new protein-based diagnostic assays. Using the antibody-independent mass-spectrometry based cell surface capturing (CSC) technology, we specifically investigated the N-glycosylated surfaceome of MPM towards the identification of protein-marker candidates di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several identified SNPs were located in or near genes that might be involved in biological pathway leading to lung function impairment (ie, GALNT13 and PCDH9, respectively). GALNT13 belongs to the GalNAcT family of enzymes, which initiate O-glycosylation of mucins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several identified SNPs were located in or near genes that might be involved in biological pathway leading to lung function impairment (ie, GALNT13 and PCDH9, respectively). GALNT13 belongs to the GalNAcT family of enzymes, which initiate O-glycosylation of mucins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teneurin-2 was shown to be expressed in the majority of malignant mesothelioma cell lines but not in lung adenocarcinoma cell lines investigated. 41,42 Mesothelioma is a rare form of cancer developing in the mesothelium, the protective body that covers many of the internal organs of the body, such as the pleura (the outer lining of the lungs and internal chest wall). Mesothelioma is most commonly caused by (occupational) exposure to asbestos.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they showed that CD90 was expressed only in the epithelioid mesothelioma (15 cases) but not in lung adenocarcinoma (61 cases) [84]. Similarly, proteomic surfaceome analysis of Nglycosylated protein in mesothelioma and lung adenocarcinoma also found CD90 to be expressed exclusively in malignant pleural mesothelioma cell lines (MSTO-211H, H2052, H2452, H226) but not in lung adenocarcinoma cell lines (Calu-3, A549, Calu-6, SK-LU-1) suggesting a role for CD90 as a diagnostic marker for mesothelioma [85]. In addition, CD90 was present along with other markers in the cells recovered from the primary xenograft of patient mesothelioma samples.…”
Section: Cd90 As Marker For Malignant Cancer Cellsmentioning
confidence: 90%
“…Using in silico analysis of transcriptomics data, we recently found evidence for altered expression of Ten-2 and Ten-4 in various tumor types [24], and expression of Ten-2 at the protein level has been detected in malignant pleural mesothelioma using a chemo-proteomic strategy [25]. Moreover, recurrent structural changes in the TENM3 gene have been identified in neuroblastoma, and low Ten-3 mRNA levels in these tumors were associated with shorter patient survival [26].…”
Section: Introductionmentioning
confidence: 99%